1993
DOI: 10.1212/wnl.43.12.2703
|View full text |Cite
|
Sign up to set email alerts
|

Sudden hearing loss as the initial monosymptom of multiple sclerosis

Abstract: Hearing loss is an uncommon symptom in multiple sclerosis. We report two patients in whom unilateral sudden hearing loss was the first monosymptomatic manifestation of multiple sclerosis. We confirmed the initial central auditory dysfunction suggested by audiometric findings and brainstem auditory evoked potentials by MRI, which showed a unilateral pontine lesion in one patient and a lesion in the medulla oblongata in the other.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 0 publications
0
14
0
1
Order By: Relevance
“…In one of them, these symptoms were the main presentation of the disease and MRI showed ipsilateral abnormalities over the parieto-occipital white matter whereas in the other patient, this occurred as a relapse and was associated with multiple widespread white matter abnormalities. Drulovic et al [13] reported two patients, both with SNHL as the first and only manifestation of MS, and with transient BAEP and MRI abnormalities; the latter consisting of a small parasaggital pontine lesion in one case and in the other, increased signal in the right side of the pontomedullary junction. Involvement of the acoustic nerve has also been demonstrated as in the case reported by Bergamaschi et al [14] where BAEPs suggested retrocochlear involvement with absent wave I and MRI showed abnormal signal with enlargement and gadolinium enhancement of the eighth nerve ipsilateral to the ear affected.…”
Section: Discussionmentioning
confidence: 99%
“…In one of them, these symptoms were the main presentation of the disease and MRI showed ipsilateral abnormalities over the parieto-occipital white matter whereas in the other patient, this occurred as a relapse and was associated with multiple widespread white matter abnormalities. Drulovic et al [13] reported two patients, both with SNHL as the first and only manifestation of MS, and with transient BAEP and MRI abnormalities; the latter consisting of a small parasaggital pontine lesion in one case and in the other, increased signal in the right side of the pontomedullary junction. Involvement of the acoustic nerve has also been demonstrated as in the case reported by Bergamaschi et al [14] where BAEPs suggested retrocochlear involvement with absent wave I and MRI showed abnormal signal with enlargement and gadolinium enhancement of the eighth nerve ipsilateral to the ear affected.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature there are several reports of MS-related hearing threshold deficits. These MS-related hearing losses occur when the MS involves the peripheral and brainstem auditory pathway (Jabbari et al, 1982;Daugherty et al, 1983;Shea and Brackmann, 1987;Franklin et al, 1989;Drulović et al, 1993;Bergamaschi et al, 1997;Oh et al, 2008). However, a well-controlled study of pure-tone thresholds concluded that they were not elevated in chronic MS.…”
Section: Pure-tone Thresholdmentioning
confidence: 99%
“…These findings imply that when MS-related hearing losses occur, they are rare, typically acute, and most commonly involve the peripheral auditory system or brainstem, in accord with numerous case reports. (Jabbari, Marsh, & Gunderson, 1982; Daugherty, Lederman, Nodar, & Conomy, 1983; Drulovic et al, 1993; Shea, III & Brackmann, 1987; Franklin, Coker, & Jenkins, 1989; Bergamaschi, Romani, Zappoli, Versino, & Cosi, 1997; Oh, Oh, Jeong, Koo, & Kim, 2008) In one study of 705 MS patients, only 1.7% exhibited hearing loss during a period of symptom exacerbation (Fischer et al, 1985). In all but one of these cases the loss was unilateral.…”
Section: Discussionmentioning
confidence: 99%